Mogroside V Improves Follicular Development and Ovulation in Young-Adult PCOS Rats Induced by Letrozole and High-Fat Diet Through Promoting Glycolysis - Huang, Lan’e; Liang, Aihong; Li, Tianlong; Lei, Xiaocan; Chen, Xi; Liao, Biyun; Tang, Jinru; Cao, Xiting; Chen, Gang; Chen, Fengyu; Wang, Yiyao; Hu, Linlin; et al. (Frontiers in Endocrinology, 2022)
Polycystic ovary syndrome (PCOS) is a heterogeneous endocrine disorder characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovaries. In this study, we induced a young-adult PCOS rat model by oral administration of letrozole combined with a high-fat diet and then treated with mogroside V (MV) to evaluate the protective effects of MV on endocrine and follicle development in young-adult PCOS rats. MV (600 mg/kg/day) administration not only significantly reduced the body weight and ovary weight, but also attenuated the disrupted estrous cycle and decreased the level of testosterone. MV restored the follicular development, especially by increasing the number of corpus luteum and the thickness of the granular layer in young-adult POCS rats. Moreover, metabolomics showed that MV markedly increased the levels of D-Glucose 6-phosphate, lactate and GTP, while decreased the level of pyruvate. Bioinformatic analysis revealed that MV recovered multiple metabolism-related processes including gluconeogenesis, glycolysis and glucose metabolic process. Further real-time quantitative PCR analysis showed that MV upregulated the expression of lactate dehydrogenase A (Ldha), hexokinase 2 (Hk2) and pyruvate kinase M2 (Pkm2). Western blotting and immunohistochemistry analysis showed that MV restored the expression of lactate dehydrogenase A (Ldha), hexokinase 2 (Hk2) and pyruvate kinase M2 (Pkm2). Collectively, these findings indicated that MV could effectively improve the ovarian microenvironment by upregulating the expression of LDHA, HK2 and PKM2 in granulosa cells and enhancing lactate and energy production, which may contribute to follicle development and ovulation of young-adult PCOS rats.